A Novel Amiodarone-Eluting Biological Glue for Reducing Postoperative Atrial Fibrillation: First Animal Trial. (September 2014) - Beckerman, Ziv; Azran, Adi; Cohen, Oved; Nir, Rony-Reuven; Maessen, Jos G.; Bianco-Peled, Havazelet; Bolotin, Gil
Objective: Postoperative atrial fibrillation (POAF) is the most common complication after cardiac surgery, leading to increased morbidity and mortality. The aim of this preliminary study was to evaluate a novel drug delivery system for local release of amiodarone. Methods: In the current prospective study, 9 goats underwent attachment of right atrial (RA) epicardial electrodes. Alginate-based glue with amiodarone was applied to the RA of the treatment groups. Rapid atrial response (RAR) to burst pacing was assessed before application and in the third postoperative day (POD3). Average RAR frequency was defined as the average percentage of inductions resulting in RAR per animal. Myocardial and extracardiac tissue amiodarone concentrations were analyzed. Results: Differences in RAR proportions between baseline and POD3 were greater in the treatment group versus the control group ( P = .034). Average RAR frequency was reduced by 34% in the treatment group (baseline: 65%; POD3: 31%), while it was increased by 11.3% in the control (baseline:43.8%; POD3: 55%). The treatment group demonstrated a greater proportion of animals meeting the success criterion of net percentage reduction in RAR frequency greater than 25% ( P = .047). The average amount of total amiodarone detected in the RA was 104.4 ± 28.9 µg; the transmural concentration was linearly distributed ( P < .0001). Extracardiac tissue concentrations were below the detection level. Conclusions: Local alginate-based amiodarone delivery demonstrated an RAR frequency reduction of clinical importance in response to burst pacing. The electrophysiological response was achieved while maintaining below-detection systemic drug levels. Current findings may point to the system's future applicability in reducing POAF risk in humans.